Rangelands data platform: Establishing the first-ever global data platform for monitoring rangelands and consolidating rangeland data - García, D.C.; Flintan, Fiona E. (University of Valencia, 2023)
Presented by Domenech Carlos and Fiona Flintan at the Identification Mission Meeting for the Lowlands Livelihood Resilience Project, Phase Two, for the World Bank and Government of Ethiopia 6 March 2023, Addis Ababa, Ethiopia